Success of Urgent-Start Peritoneal Dialysis in a Large Canadian Renal Program. Issue 2 (March 2016) - Alkatheeri, Ali M.A.; Blake, Peter G.; Gray, Daryl; Jain, Arsh K.
Background: Many patients start renal replacement therapy urgently on in-center hemodialysis via a central venous catheter, which is considered suboptimal. An alternative approach to manage these patients is to start them on peritoneal dialysis (PD). In this report, we describe the first reported Canadian experience with an urgent-start PD program. Additionally we reviewed the literature in this area. Methods: In this prospective observational study, we report on our experience in a single academic center. This program started in July 2010. We included patients who initiated PD urgently, that is within 2 weeks of catheter insertion. We followed all incident PD patients until October 2013 for mechanical and infectious complications. Peritoneal dialysis catheters were inserted either percutaneously or laparoscopically and dialysis was initiated in either an inpatient or outpatient setting. Results: Thirty patients were started on urgent PD during our study period. Follow-up ranged from 28 to 1, 050 days. Twenty insertions (66.7 %) were done percutaneously and 10 (33.3%) were laparoscopic. Dialysis was initiated within 2 weeks (range: 0 – 13 days, median = 6 days). Twenty-four patients (80%) started PD in an outpatient setting and 6 patients (20%) required immediate inpatient PD start. Three patients (10%) developed a minor peri-catheter leak during the first week of training that was managed conservatively. There were no episodes of peritonitis or exit-site/tunnel infection during the first 4 weeks post-insertion. Four patients (13.3 %) from the percutaneous insertion group and 2 patients (6.7%) from laparoscopic insertions developed catheter dysfunction due to migration, which was managed by repositioning, without need for catheter replacement or modality switch. Conclusions: Our results are consistent with other studies in this area and demonstrate that urgent-start PD is an acceptable and safe alternative to hemodialysis in patients who need to start dialysis urgently without established dialysis access.